The Dead Sea Scrolls at 60: Scholarly Contributions of New York University Faculty and Alumni - Schiffman, Lawrence H. (Studies on the Texts of the Desert of Judah Ser., 2010)
This volume constitutes the proceedings of the 2008 Ranieri Colloquium on Ancient Studies at New York University, dedicated to "The Dead Sea Scrolls at 60: The Scholarly Contributions of NYU Faculty and Alumni.".